2019
DOI: 10.1111/jre.12721
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3+ and CD25+ cells are reduced in patients with stage IV, grade C periodontitis: A comparative clinical study

Abstract: Background and Objective Some studies suggest that regulatory T cells (Tregs) have suppressive effects on inflammatory osteolysis. The aim of this study was to evaluate Treg immunomarkers in periodontitis‐affected tissues from patients with periodontitis and clinically healthy gingiva (control). Material and Methods The presence and distribution of positive cells for CD4, CD25 and FOXP3 (Treg immunomarkers) in periodontitis‐affected tissues (epithelium and lamina propria) of 30 patients (ten per group) with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…We demonstrate a significant increase in CD25+ B cell proportion, which is different from CD25+ Tregs (Cafferata et al., 2019). The researcher proved an obvious decrease in CD25+ Tregs during periodontitis (Motta et al., 2020). Generally, Tregs suppress over excessive inflammation and protect periodontal tissue from inflammatory injury.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate a significant increase in CD25+ B cell proportion, which is different from CD25+ Tregs (Cafferata et al., 2019). The researcher proved an obvious decrease in CD25+ Tregs during periodontitis (Motta et al., 2020). Generally, Tregs suppress over excessive inflammation and protect periodontal tissue from inflammatory injury.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the level of Foxp3 + T cells is increased in periodontitis. However, Da Motta et al found that as periodontitis progresses, the percentage of functionally active Tregs (CD25/Foxp3 double‐positive cells) decreases 122 . In periodontitis lesions, CD25/Foxp3 double‐positive Tregs are actually FoxP3 bright cells, unlike FoxP3 single‐positive cells (FoxP3 dim cells) and CD25 single‐positive cells (Foxp3 − cells), two other cell types in periodontal tissue 123 .…”
Section: The Conversion Of Treg Into Th17 Cells Promote Bone Resorptionmentioning
confidence: 99%
“…Human stem cells from the apical papilla stimulated the conversion of CD4 + CD25 − T cells to CD4 + CD25 + Foxp3 + Tregs in vitro; Tregs were also enriched around regenerating tissue in the root canals of beagles with apical periodontitis induced in experimental immature teeth following regenerative endodontic treatment 43 . Exosomes extracted from periodontal ligament stem cells (PDLSCs) of healthy subjects showed an abundance of Tregs and a reduced number of Th17 cells, whereas the opposite was observed in exosomes from PDLSCs incubated with LPS, which had a lower level of miR‐155‐5p and higher level of sirtuin (SIRT)1 than those extracted from normal PDLSCs.…”
Section: Phenotypes and Roles Of Tregs In Periodontitismentioning
confidence: 98%
“…Phenotypes (controversial): ↑Treg in gingival tissues 169 42 ; ↑Treg and ↑Th17/Treg ratio in peripheral circulating 170 41 ; More Treg in gingival tissues of patients (stage III, grade B VS stage IV, grade C) 43 ; ↓Treg, ↓TGF‐β1 and IL‐10 mRNA in active periodontal lesions 44 47 ; ↓Tregs in spleen 47 ; ↓CD4 + Foxp3 + while ↑IL‐17A + Foxp3 + in periodontitis lesions 171 …”
Section: Phenotypes and Roles Of Bregs In Periodontitismentioning
confidence: 99%
See 1 more Smart Citation